The impact of anthropometric characteristics on isometric trunk muscle endurance tests: A reliability and performance analysis - Casto Juan-Recio; Francisco J. Vera-Garcia; Alejandro Lopez-Valenciano; David Barbado (PLoS ONE, 2025)
The Biering-Sorensen test (BST), the Side Bridge test (SBT) and the Ito test (IT) are three of the most used field-based tests to assess isometric trunk muscle endurance. The objectives were to analyze the relationship between the participants’ test performance and several anthropometry parameters, the data consistency and the sex effect on test scores. Forty-five recreational athletes (27 males and 18 females) performed the three isometric trunk holding tests twice in two testing sessions to perform the reliability analysis and later, the three tests were performed once more, but in different sessions (one for each test) to maximize test performance and reduce the bias of muscle fatigue. Data (i.e., test scores and anthropometric variables) were logarithmic transformed to ensure the normality and homoscedasticity assumption. Relative reliability was very good, with ICCs > 0.70 in all tests, while absolute reliability showed high values of typical error (12.1–24.1%). ANOVA showed significant differences between sessions for the BST and the SBT scores and between sexes in the BST (females: 193.7 ± 53.2 s; males: 161.9 ± 52.2 s). IT scores showed a negative correlation with mass in both sexes (males: r = −.436; p = .026; females: r = −.562; p = .019) and with biileocrestal breadth (r = −.735; p = .001) and biacromial breadth (r = −.745; p = .001) in females. BST scores correlated significantly with biacromial breadth (r = −.379; p = .050) in males. SBT scores were negatively correlated to mass (r = −.703; p < .001), biileocrestal breadth (r = −.672; p < .001), biacromial breadth (r = −.601; p = .001) and acromion-iliac index (r = −.493; p = .010) in males and to relative lower extremity length (r = −.493; p = .038) in females. In conclusion, trainers and clinicians should consider individual anthropometric and sex differences when interpreting test results, as larger body mass and upper body breadth may artificially lower endurance scores. Adjustments to normative values may be required in applied settings. Moreover, based on the reliability analysis, these tests could be used to classify participants consistently, but the BST and the SBT require an extensive familiarization period and they don’t seem to be useful to detect small changes in participants’ performance over time.